Organizational capacity and project dynamics - Dana Foarta; Michael M. Ting (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2023)
This paper develops a dynamic theory of the interaction of organizational capacity and its institutional context. Higher capacity enables organizations to deliver projects efficiently, while institutional barriers allow opposing interests to reallocate project payoffs at the cost of delays. Projects that are small and distributionally unequal are vulnerable to revisions. Project designers avoid revisions by equalizing distributive benefits or inflating project scales to increase the cost of revisions. We show that "matched" levels of capacity and institutional barriers minimize welfare. Organizational systems with high capacity and low institutional barriers, or low capacity and high institutional barriers, generate more efficient outcomes.
Keywords: D73; D82; 330; Organizational Capacity; Revisions; Power Transitions; Project Delays; Project Design